Determinação de compostos bioativos em sistemas microalgais - Caetano, Patrícia Acosta (2022)
Microalgae are a diverse source of bioactive molecules and are widely used in the food, chemical and pharmaceutical industries. Carotenoids are important compounds known for their bioactive activities. Among the best-known carotenoids, β-carotene is the most used commercially. However, lutein has been growing positively in the market, mainly because it is the only carotenoid able to accumulate in a specific location inside the human body, the eye macula. Microalgae are recognized as natural sources of carotenoids, which are commonly produced by photoautotrophic cultures. On the other hand, heterotrophic systems for the production of natural pigments have been showing potential for commercial applications, as they help to overcome difficulties associated with CO2 supply and light incidence. In addition, heterotrophic models contribute to the prevention of contamination issues. In this sense, this work intended to evaluate the (i) metabolic versatility of the microalgae Chlorella vulgaris in different microalgal systems and (ii) to evaluate the behavior of carotenoids as a function of the growth curve in the heterotrophic cultivation, as a source of exogenous carbon, glucose. The results showed a profile of 23 compounds with significant qualitative and quantitative changes at times 0, 4, 12, and 96 h, reaching a maximum cell biomass of 2200mg.L-1 and productivity of 12.15 mg.L.h-1 and it was observed a significant increase in total carotenoid content by 1612.02μg.g-1 in the first 4 hours. The main carotenoids in all extracts were all-trans-lutein and all-trans-β-carotene. According to these results, it was verified that carotenoids can be synthesized in the dark and that heterotrophic cultures are interesting options for commercial production of lutein, since they show advantages, such as high content of free lutein and better growth rate.